2015
DOI: 10.1007/s10545-014-9809-1
|View full text |Cite
|
Sign up to set email alerts
|

First two unrelated cases of isolated sedoheptulokinase deficiency: A benign disorder?

Abstract: We present the first two reported unrelated patients with an isolated sedoheptulokinase (SHPK) deficiency. The first patient presented with neonatal cholestasis, hypoglycemia, and anemia, while the second patient presented with congenital arthrogryposis multiplex, multiple contractures, and dysmorphisms. Both patients had elevated excretion of erythritol and sedoheptulose, and each had a homozygous nonsense mutation in SHPK. SHPK is an enzyme that phosphorylates sedoheptulose to sedoheptulose-7-phosphate, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Results show that 7 genes ( PPP2R1B, BCKDHA, EPB41L4A, GOLGA6L10, SHPK, ST3GAL6, and UTS2R ) are expressed in testis, but none of these mouse models is correlated with fertility except Ppp2r1b ‐deficient mice designed by ourselves. To further explore the role of these 12 genes, we have done literature review, and the result shows that none of related literatures is reported on fertility 39‐49 . Thus, PPP2R1B mutation is likely correlated to non‐obstructive azoospermia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results show that 7 genes ( PPP2R1B, BCKDHA, EPB41L4A, GOLGA6L10, SHPK, ST3GAL6, and UTS2R ) are expressed in testis, but none of these mouse models is correlated with fertility except Ppp2r1b ‐deficient mice designed by ourselves. To further explore the role of these 12 genes, we have done literature review, and the result shows that none of related literatures is reported on fertility 39‐49 . Thus, PPP2R1B mutation is likely correlated to non‐obstructive azoospermia.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the role of these 12 genes, we have done literature review, and the result shows that none of related literatures is reported on fertility. [39][40][41][42][43][44][45][46][47][48][49] Thus, PPP2R1B mutation is likely correlated to non-obstructive azoospermia.…”
Section: Ppp2r1b Mutations Are Identified In the Cases Of Human Non-obstructive Azoospermiamentioning
confidence: 99%
“…The plasticity of macrophage polarization allows them to fulfill numerous biological functions ranging from pro-inflammatory roles classified as either pro-inflammatory mediator of a type I immune response (M1 macrophages), to tissue repair, homeostasis and resolution of inflammation (M2 macrophages) [ 29 , 30 ]. In the context of our stem cell trial for cystinosis, an important function of SHPK was reported by Haschemi and colleagues on its involvement in macrophage polarization [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In transketolase deficiency, hepatic abnormalities are rare, and neither hyper- nor hypo-coagulation were reported [ 21 , 30 ]. Another genetic inborn error of PPP, sedoheptulo kinase deficiency (encoded by SHPK), is also characterized by increased endogenous erythritol synthesis [ 38 ] and increased urinary erythritol [ 38 , 39 ]. The available case report described two patients, and coagulation abnormalities were not reported [ 38 ].…”
Section: Erythritol Exposure Due To Inborn Errors Of Pentose Phosphat...mentioning
confidence: 99%